A comprehensive treatment for peritoneal metastases from gastric cancer with curative intent. Issue 8 (August 2016) - Yonemura, Y.; Canbay, E.; Li, Y.; Coccolini, F.; Glehen, O.; Sugarbaker, P.H.; Morris, D.; Moran, B.; Gonzaletz-Moreno, S.; Deraco, M.; Piso, P.; Elias, D.; et al.
Abstract: Recently, Peritoneal Surface Oncology Group International (PSOGI) developed a novel comprehensive treatment consisting of cytoreductive surgery (CRS) and perioperative chemotherapy (POC) for the treatment of peritoneal metastases (PM) from gastric cancer with curative intent. This article reviews the results of this treatment and verifies its indication. In this strategy, peritoneal cancer index (PCI) is determined by laparoscopy, and a peritoneal port is placed. Neoadjuvant bidirectional intraperitoneal/systemic chemotherapy (NIPS) is performed for 3 cycles, and then laparotomy is performed. Cytoreductive surgery with peritonectomy procedures and hyperthermic intraperitoneal chemoperfusion (HIPEC) are performed. Multivariate analyses showed that completeness of cytoreduction, pathologic response to NIPS and PCI level and cytologic status after NIPS, as independent prognostic factors. PCI less than cut-off level after NIPS, negative cytology after NIPS, and positive response to NIPS were identified as the indications for comprehensive treatment. Patients who hold these criteria should be considered as the candidates for CRS and HIPEC. Abstract : Peritoneal metastases of gastric cancer can be treated with combined treatment approach when the patient have PCI level less than 6, negative cytology, and a positive response to neoadjuvant chemotherapy.